Works Councils as Gatekeepers: Codetermination, Monitoring Practices, and Job Satisfaction - Christian Grund; Dirk Sliwka; Krystina Titz (Institute of Labor Economics (IZA), 2023)
This paper analyzes the role of works councils as gatekeepers safeguarding employee's interests in the adoption of monitoring practices. We first introduce a formal model predicting that (i) the introduction of monitoring practices leads to a stronger increase (or weaker decrease) in job satisfaction when a works council is in place, (ii) that this effect should be larger the lower the prior level of employee participation and (iii) that works councils increase the likelihood of the implementation of monitoring practices at the level of individual employees. We provide evidence in line with these hypotheses using linked-employer-employee panel data from Germany. We indeed find that the adoption of formal performance appraisals and feedback interviews is associated with a significantly larger increase in job satisfaction when there is a works council. This pattern is driven by establishments without collective bargaining agreements. The evidence also suggests that works councils indeed facilitate the implementation of monitoring practices, as codetermined firms have a higher likelihood that a practice implemented on the firm level is actually applied by middle management.
Keywords: M5; J83; J28; 330; works councils; codetermination; performance appraisal; feedback interview; job satisfaction; linked employer-employee data